2016
DOI: 10.4070/kcj.2016.46.6.821
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Platelet/Lymphocyte Ratio and Coronary Artery Disease Severity in Asymptomatic Low Ejection Fraction Patients

Abstract: Background and ObjectivesCoronary angiography (CAG) is generally needed in the setting of systolic heart failure (HF) with an unidentified etiology as a part of diagnostic strategy. On the other hand, the clinical value of this invasive strategy is largely unknown. Platelet-lymphocyte ratio (PLR) has recently emerged as a novel inflammatory index that may serve as an important predictor of inflammatory state and overall mortality. The present study aimed to search the predictive value of PLR in determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…We have found that NLR was a more useful marker at ROC curve, similar to studies in HF. 28,29 Besides, in our study, NLR-but not PLR-was independently associated with 1 year mortality on multivariate analysis, in accordance with one study in HF. 28 Moreover, NLR was also associated with increased in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We have found that NLR was a more useful marker at ROC curve, similar to studies in HF. 28,29 Besides, in our study, NLR-but not PLR-was independently associated with 1 year mortality on multivariate analysis, in accordance with one study in HF. 28 Moreover, NLR was also associated with increased in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Although both markers have shown prognostic value in several cardiac conditions, few studies have compared them. We have found that NLR was a more useful marker at ROC curve, similar to studies in HF 28, 29. Besides, in our study, NLR—but not PLR—was independently associated with 1 year mortality on multivariate analysis, in accordance with one study in HF 28.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations